Non-Invasive Laser Technologies for Early Detection of Oral Cancer and Dental Diseases - Vijayalakshmi Gachinamath; Alluri Siddhartha Varma; Rashmi Gangavati; Parvati Huded (Oral Sphere Journal of Dental and Health Sciences, 2026)
Early and accurate detection of oral diseases, particularly oral cancer, remains a cornerstone of effective management and improved survival. Conventional diagnostic methods, though reliable, are limited by invasiveness and subjectivity. Recent advances in laser- and light-based technologies provide non-invasive, real-time tools for detecting pathological changes. DIAGNOdent enhances early caries detection with high sensitivity but moderate specificity. Optical coherence tomography (OCT) produces high-resolution cross-sectional images, proving valuable in lesion assessment and biopsy guidance. Autofluorescence devices enable rapid chairside screening, although false positives are common. Raman spectroscopy demonstrates exceptional accuracy for cancer detection and surgical margin assessment, while emerging modalities such as laser-induced breakdown spectroscopy, photoacoustic imaging, and diffuse optical techniques show promising yet experimental applications. Laser Doppler flowmetry has established utility in pulp vitality testing. Collectively, these modalities complement traditional diagnostic approaches, and future integration of artificial intelligence is expected to further enhance diagnostic accuracy and clinical adoption.